-4(2n+6)=16

Simple and best practice solution for -4(2n+6)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2n+6)=16 equation:


Simplifying
-4(2n + 6) = 16

Reorder the terms:
-4(6 + 2n) = 16
(6 * -4 + 2n * -4) = 16
(-24 + -8n) = 16

Solving
-24 + -8n = 16

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + -8n = 16 + 24

Combine like terms: -24 + 24 = 0
0 + -8n = 16 + 24
-8n = 16 + 24

Combine like terms: 16 + 24 = 40
-8n = 40

Divide each side by '-8'.
n = -5

Simplifying
n = -5

See similar equations:

| a+2c=4b-5 | | 6x^2-2=-11x | | 125*e(-0.2x)=0 | | 3x+2(x-7)=4x-7 | | -3x^2-18x-15=0 | | 60-4.5d=44-3.5d | | 125*exp(-0.2x)=0 | | 0.50x+0.65(60)=0.25(86) | | 4586=(165x)+2771 | | 5n+3(n-7)=-(n+8) | | 6a-5=8a-7 | | 88-5x=53 | | 12p+13p+21p=8970 | | -9(v+4)+2v+6=5v+6 | | 4-8x=4+3x | | -17x+2=-19x+18 | | c-19.2=240 | | 30+2.5x=20-1.5x | | (2*-3.5+7)(-3.5+6)= | | x+(40/2)=27 | | 60+2x=74 | | 5x+7=25y+7 | | 600+x(20)=4200 | | 4x+5(2)=14 | | y=0.01x-0.001x^2 | | -.05x^2+2.7x+5.5=0 | | x+1855.3=4360.3 | | 2a^2+4a-48=2 | | (-2+3y)-(6y-4x)= | | x+40/2=27 | | 26+1=9 | | 8x+59=-9x-8 |

Equations solver categories